Design and analysis of double stator HE-FSM for aircraft applications - Hassan Ali; Erwan Sulaiman; Mahyuzie Jenal; Irfan Ali; Laili Iwani Jusoh; Zarafi Ahmad; Mohd Firdaus (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The main objective of aerospace industry is to produce all electric aircraft (AEA) equipped by electrical devices in coming developments. Electrical machines that provide higher torque densities are gaining more interest for researchers to obtain sustainable direct-drive electrical propulsion system for aircraft applications. In addition to lesser weight and higher torque density, a machine should be “fault tolerant” to applied in aerospace applications. A novel machine for high starting torque, identified as flux switching machine (FSM) was established over the last decade. FSMs comprise all effective sources on stator including robust rotor structure. These machines exhibited higher “torque-to-weight ratios” and reliability. Nonetheless, the challenge of developing a machine suitable for aircraft applications goes far beyond electromagnetic design and much deeper into the field of mechanical systems than traditional ones. Thus, a new double stator (DS) hybrid excitation (HE) FSM design employing segmented rotor is proposed and analyzed in this research work. The suggested design for DS HE-FSM comprises of six field excitation coils (FECs) and six permanent magnets (PMs) as their excitation sources. In this research, investigation of DS HE-FSM is accomplished with respect to flux linkage, back EMF, cogging torque and torque analysis based on 2D FEA.